Perbandingan Performa dan Volatilitas JII dan IHSG Periode 2020-2025 di Indonesia - Riswanti, Riswanti; Rohmi, Misfi Laili; Apridasari, Esty; Ismail, Vera (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The Indonesian capital market experienced significant pressure, particularly during the early period of the COVID-19 pandemic, followed by a recovery phase amid persistently high global economic uncertainty. These conditions affected the performance and volatility of stock indices, both conventional and Sharia-based indices. This study aims to analyze and compare the performance and volatility of the Composite Stock Price Index (IHSG) and the Jakarta Islamic Index (JII) during the 2020–2025 period in Indonesia. The novelty of this research lies in the integration of performance and volatility analysis within a single comparative framework, as well as its focus on both crisis and economic recovery phases simultaneously, which remains limited in previous empirical studies. This study employs a quantitative approach with a descriptive-comparative method using secondary data in the form of monthly closing prices of IHSG and JII. Index performance is measured using average monthly returns, while volatility is analyzed through variance and standard deviation. The results show that IHSG has an average monthly return of 0.005134, while JII records −0.001511. These findings indicate that IHSG demonstrates better performance compared to JII, as it yields a positive return, whereas JII shows a negative return during the study period. In terms of risk, JII exhibits a higher level of volatility compared to IHSG. These findings suggest that Sharia stock indices do not always have lower risk than conventional indices, particularly under conditions of economic uncertainty, and highlight the importance of considering index structure in investment decision-making. The implications of this study are that investors, both conventional and Sharia, need to conduct more in-depth analyses of the risk and return characteristics of each index before making investment decisions. Furthermore, this research contributes to regulators and index providers in evaluating the stability and competitiveness of Sharia indices within the dynamics of the global capital market.